Exploring labour-based approach for rural road maintenance in Nigeria (2008)
Rural roads are very cardinal to the socio-economic development of the rural population. They enhanced increased agricultural production, facilitate access to educational and health facilities and provide spatial interaction among rural communities. However, in Nigeria, the condition of rural roads is pathetic. More than 70% of rural road network is in deplorable condition, which is due partly to inadequate finance, weak technical knowhow of personnel, the use of heavy equipment, official corruption and most importantly lack of political will by the government or its agencies. The consequences are disruption of socio-economic activities of the rural inhabitants. Therefore, the adoption of Labour- Based Approach which is participatory in nature and utilizes local knowledge and initiatives as well as requiring little resources could be the panacea to the protracted deplorable and deteriorating condition of rural roads in the country. The approach will not only improve the quality of life of the rural populace through the creation of job opportunities for the teeming rural population and lowering of transport cost, it will also ensure the sustainable maintenance of rural roads in the country.